(untitled) (Revista Logos Ciencia & Tecnología, 2019)
Teacher’s discomfort and School violence phenomena are contemporary. The first one was implemented by Olweus in 1978 and the second by Esteve in 1987. There are few studies about this relationship, however from the beginning of the 21st Century the school violence towards the Teachers have been documented. In the documental revision of the topic, including legal papers, a database and a reference database were created to analyse the content in order to identify the chances in the education system and Teachers Development as a relevant pedagogical relationship in which the teacher is removed from their knowledge-pedagogical base generating to be seen as victims, health problems and even, professional illnesses.